Banker to the third world : US portfolio investment in Latin America, 1900-1986 - Stallings, Barbara (Oakland, CA : University of California Press, 2018)
By the end of 1985, Latin Americans owed their foreign creditors 368 billion. That was nearly 1,000 for every man, woman, and child between the Rio Grande and Tierra del Fuego. The debt represented more than half of the region's gross domestic product, and interest payments alone consumed 36 percent of export revenues. If profits are added to interest, and the total compared to new capital inflows, the drama of the situation becomes clear: a real resource tran.
The Financial Crisis of the 1980s -- Appendixes. Statistical Data, Sources, and Methodology -- I. Capital Flow Series -- II. U.S. Economic Series -- III. Latin American Regional Economic Series -- IV. Latin American Country Economic Series -- V. Data Bank on International Loans -- Bibliography -- Index
Originally published in 1987.
Includes bibliographical references (pages 379-422) and index.
Print version record.
JSTOR
Keywords: Investments, American -- Latin America -- History; Loans, American -- Latin America -- History; SOCIAL SCIENCE / Anthropology / Cultural & Social; Investments, American; Loans, American; Latin America; History